Diminished Functional Connectivity on the Road to Child Sexual Abuse in Pedophilia. (23rd January 2015) - Kärgel, Christian; Massau, Claudia; Weiß, Simone; Walter, Martin; Kruger, Tillmann H.C.; Schiffer, Boris
Abstract Background Pedophilia is a disorder recognized for its impairment to the individual and for the harm it may cause to others. However, the neurobiology of pedophilia and a possible propensity to sexually abuse children are not well understood. In this study, we thus aimed at providing new insights in how functional integration of brain regions may relate to pedophilia or child sexual abuse (CSA). Method By using functional magnetic resonance imaging (fMRI) technique, we compared functional connectivity at rest (RSFC) between pedophiles who engaged (P+CSA; N = 12) or did not engage (P–CSA; N = 14) in CSA and healthy controls (HCs; N = 14) within two networks: (i) the default mode network and (ii) the limbic network that has been linked to pedophilia before. Results Pedophiles who engaged in CSA show diminished RSFC in both networks compared with HC and P–CSA. Most importantly, they showed diminished RSFC between the left amygdala and orbitofrontal as well as anterior prefrontal regions. Though significant age differences between groups could not be avoided, correlation control analysis did not provide evidence for the assumption that the RSFC effects were related to age differences. Conclusion We found significantly diminished RSFC in brain networks critically involved in widespread motivational and socio‐emotional processes. These results extend existing models of the functional neuroanatomy of pedophilia and CSA as altered RSFC between these regions were related to CSA rather than pedophilia and thus may account for an increased propensity to engage in CSA in people suffering from pedophilia. Kärgel C, Massau C, Weiß S, Walter M, Kruger THC, and Schiffer B. Diminished functional connectivity on the road to child sexual abuse in pedophilia. J Sex Med 2015;12:783–795.